Hemophagocytic lymphohistiocytosis of indeterminate cause: a fatal adult case - Fernando Peixoto Ferraz de Campos; Elizabeth In Myung Kim; Luciana Andréa Avena Smeili; Patrícia Picciarelli de Lima; Fabiana Roberto Lima; Angélica Braz Simões; Maria Claudia Nogueira Zerbini (University of São Paulo, 2012)
Hemophagocytic lymphohistiocytosis (HLH) is an uncommon life-threatening disorder characterized by wide spread non-neoplastic proliferation and inappropriate activation of mature macrophages resulting in hypercytokinemia. This uncontrollable and ineffective systemic immune response causes fever, hepatosplenomegaly, cytopenias and subsequently multiorgan failure. The authors report a case of a 41-year-old male patient with a 30-day history of weight loss, fever, icterus, hepatomegaly, and cytopenias. The diagnostic workup disclosed hypertriglyceridemia, hypofibrinogenemia, and elevated ferritin. Bone marrow examination and clinical course raised the suspicion of HLH and treatment was started with high-dose corticosteroids and immune globulin. The patient underwent multi-organ failure and expired after 58 days of hospitalization. The autopsy finding included massive bone marrow infiltration by non-neoplastic histiocytes, many of them showing hemophagocytosis, which immunohistochemical study revealed diffuse CD68-positive histiocytes, which were negative for S100 protein. Hemophagocytosis was also observed in the lungs, lymph nodes and liver. The immediate cause of death was attributed to a massive intestinal bleeding due to extensive ischemic necrosis at the duodenum/jejunal transition area.